Impact of the mining industry on the mental health of landholders and rural communities in southwest Queensland. (February 2013) - Hossain, Delwar; Gorman, Don; Chapelle, Betti; Mann, Wayne; Saal, Rod; Penton, Geoff
Objective: We aimed to ascertain the extent of mental health problems in rural communities of southwest Queensland. Methods: Twelve workshops were conducted within this region, asking community members about the issues which were affecting their mental health, the gaps in services and facilities, and suggestions as to how to strengthen their capacity to deal with mental health problems. Results: The participants highlighted the higher cost of living through increased rental and goods and services costs. Non-resident workforces, putting a strain on housing availability and succession planning, were among key concerns. The rapid increase in population has also put strains on health services within these communities, highlighting the need for mental health resources and a greater clarification and coordination of available health services. Conclusions: The rural communities in this region are under sustained stress resulting from the incursion of the mining and coal seam gas industries. This has an impact on community mental health and wellbeing.